Implementation of strengthening the Pancasila student profile in driving schools to improve understanding, appreciation, and application of Pancasila values - Lestari, Hasanah Dewi; Pudjiati, Indri; Marwa, Neneng Widya Sopa; Anas, Brian; Rasyid, Muhammad; Hidayat, Otib Satibi (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to analyze the implementation of the project to strengthen the profile of Pancasila students in the driving school. The project aims to improve the understanding, appreciation, and application of Pancasila values in students. The type of research used uses descriptive research using a qualitative approach so that data collection is obtained through interviews, observations, and document analysis. The data obtained will be analyzed in depth using the data analysis technique of the Miles & Huberman model (1994) to identify factors that influence the success of project implementation and evaluate its impact on the profile of Pancasila students. The results showed a significant positive impact on students who refer to the elements or dimensions of the Pancasila Student Profile. This research is expected to provide valuable insights and recommendations for education stakeholders in developing similar programs in other schools.